Computer Networking Company in Business Area - Aisyah, Siti (International Research Journal of Management, IT & Social Sciences, 2015)
Computer Networking is not something new today. Almost every company there is a Computer Network to facilitate the flow of Information within the company. Internet increasingly popular today is a giant Computer Network of Computers that are connected and can interact. This can occur because of the network technology development is very rapid. But in some ways connected to the internet can be dangerous threat, many attacks that can occur both within and outside such as Viruses, Trojans, and Hackers. In the end the security of computers and computer networks will play an important role in this case. A good firewall configuration and optimized to reduce these threats. Firewall configuration there are 3 types of them are screened host firewall system (Single- homed bastion), screened host firewall system (Dual-homed bastion), and screened subnet firewall. And also configure the firewall to open the ports Port right to engage connect to the Internet, because the ports to configure a firewall that can filter packets incoming data in accordance with the policy or policies. This firewall architecture that will be used to optimize a firewall on the network.